Patents and Innovation: An Empirical Study - Mansfield, Edwin (Management Science, 1986)
To what extent would the rate of development and introduction of inventions decline in the absence of patent protection? To what extent do firms make use of the patent system, and what differences exist among firms and industries and over time in the propensity to patent? These questions are in need of much more study. This paper, which reports the results of an empirical investigation based on data obtained from a random sample of 100 U.S. manufacturing firms, provides new findings bearing on each of these questions.